O conceito de catarse na filosofia de Theodor Adorno : desdobramentos para uma teoria crítica da educação - Oliveira, Tamiris Souza de (2013)
This research is a theoretical literature that has as its axis the theoretical foundations of education and concern with the relationship between educational theory and critical aestheticcultural training. One wonders about the potential that has the category catharsis present in aesthetic theory of the german philosopher Theodor Adorno to scale discussion of aesthetic and cultural formation and critical appropriation of the products of the culture industry in the school. We started from the hypothesis that the central concept of catharsis Adorno can be fruitful for the unfolding of a critical theory of education. With the mapping of the presence of the concept of catharsis in educational discussions it was noted that the category is present, however little explored. With the study of the category, we have seen that it can be powerful and critical to understanding the cathartic process operated by the culture industry and its influences in the school environment. Besides the concept constitute a possibility of relating school content and form, manifested in the masterpiece, capable of adding a historical dimension of the civilizing process of mankind, and as a way able to manifest not as a mere extension of the daily lives of students, but a possibility of distancing himself and the consequent bridge to the imagination